Un modelo de actividad con radicales: posibilidad de explorar el razonamiento abductivo y la creatividad en las clases de matemáticas - Caires Brandão, Ana Karine Dias (2018)
This article aims to discuss a possibility to explore abductive reasoning in mathematics classes with emphasis on the creation of a model of interdisciplinary activity. To achieve this, we modeled an activity involving the mathematical object, radical, content related to the 9th grade of elementary school, associating it with the disciplines of history, arts, physics and geography using as a generating theme the number, the ratio and the golden rectangle present in Renaissance works. We analyzed the abductive and creative aspects that could be explored taking as theoretical basis the Semiotics developed by Charles Sanders Peirce and the formal thought of Gilles-Gaston Granger. As a result we infer that although the content has formal rules and procedures it is possible to develop activities that enable meanings and senses for the students; the possibility of creating projects in which the generating theme is a mathematical object.